2004
DOI: 10.1159/000078402
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition Is Associated with Increased Blood Pressure in Childhood

Abstract: Background/Aims: Protein-energy malnutrition remains a major public health problem in many countries. Scanty information is available about the effects of malnutrition during childhood on blood pressure (BP). Methods: In a cross-sectional study we assessed the BP of 172 children older than 2 years living in shantytowns in São Paulo city. Ninety-one children were malnourished (height-for-age or weight-for-age Z-score below –1 of the NCHS references); 20 had recovered from malnutrition after an average time of 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
41
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 13 publications
5
41
1
2
Order By: Relevance
“…In contrast to the findings of the present study, Sesso et al 13 conducted a crosssectional study with 172 children over 2 years of age; of these, 91 were classified as malnourished with a Z-score of −1 in relation to height and weight for their age. Of the group of malnourished children, 29% showed an increase in SBP and DBP after adjustment for age, sex, and height when compared with the control children (2%).…”
Section: Discussioncontrasting
confidence: 87%
“…In contrast to the findings of the present study, Sesso et al 13 conducted a crosssectional study with 172 children over 2 years of age; of these, 91 were classified as malnourished with a Z-score of −1 in relation to height and weight for their age. Of the group of malnourished children, 29% showed an increase in SBP and DBP after adjustment for age, sex, and height when compared with the control children (2%).…”
Section: Discussioncontrasting
confidence: 87%
“…Briefly, we found that nutritional stunting, a factor previously reported to increase the risk of hypertension [7][8][9] Values are expressed as mean, with the (95% CI given in parenthesis and later obesity [5], was associated with high ACE activity in childhood and that the adjustment by gender did not modify the strength of this association. Additionally, a greater percentage of stunted children had increased BP levels, and this clinical parameter was inversely correlated with anthropometric indicators.…”
Section: Discussionmentioning
confidence: 99%
“…However, childhood malnutrition remains extremely common in many developing countries, and associations with later disease need to be established. In fact, childhood nutritional stunting, an indicator of chronic malnutrition, has been suggested as one factor that can contribute to high incidences of obesity [5], impaired glucose metabolism [6] and hypertension [7][8][9] in developing countries. A series of studies in Brazil demonstrated that alterations in blood pressure (BP) levels are associated with stunted growth in children, adolescents and adults.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 However, malnutrition is also associated with increased Blood Pressure. 9 Protein Energy Malnutrition remains a major public health problem in many countries including India, but there is scanty information available about the effects of malnutrition on blood pressure. Low socioeconomic status is associated with higher blood pressure.…”
Section: Introductionmentioning
confidence: 99%